Demorest's Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1882)
Demorest's Family Magazine. Approx year 1882, other information unknown. -- The Admiral's Ward -- Asleep-Hush! -- The Improvised Closet -- An Adventure in Peru -- Happy Hours -- Talks with Women -- A Trip to the West -- A Trial of Patience -- The Legend of the Saracelli: or Poor Sister -- The Plantin Museum at Antwerp -- His Gift -- Titles, Addresses, and Cards -- What She Wore when She was Married -- How to Treat Our Doors -- Home Art and Home Comfort -- Woman's Work and Woman's Wages -- Salem Witchcraft -- Current Topics -- What Women are Doing -- Kitchen -- Diamonds of Thought -- Spice Box -- Mirror of Fashions -- Ladies' Club
Mme Demorest's Mirror of Fashions
New York Illustrated News
Cover page, month, year, volume, and issue number are all unknown and missing from original document. Physical document begins on page 770.
Keywords: Demorest's Family Magazine; Magazine; Illustrated Periodicals; Periodicals; Travel; Dressmaking; Homemaking; Needlework; Women; Catalogue; Catalogue; Social History; Women's History; Fashion; United States; 1800s; 19th Century